Visible light-driven H(2) production by hydrogenases attached to dye-sensitized TiO(2) nanoparticles. - Reisner, E; Powell, D; Cavazza, C; Fontecilla-Camps, J; Armstrong, F (2009)
A study of hybrid, enzyme-modified nanoparticles able to produce H(2) using visible light as the energy source has been carried out to establish per-site performance standards for H(2) production catalysts able to operate under ambient conditions. The [NiFeSe]-hydrogenase from Desulfomicrobium baculatum (Db [NiFeSe]-H) is identified as a particularly proficient catalyst. The optimized system consisting of Db [NiFeSe]-H attached to Ru dye-sensitized TiO(2), with triethanolamine as a sacrificial electron donor, produces H(2) at a turnover frequency of approximately 50 (mol H(2)) s(-1) (mol total hydrogenase)(-1) at pH 7 and 25 degrees C, even under the typical solar irradiation of a northern European sky. The system shows high electrocatalytic stability not only under anaerobic conditions but also after prolonged exposure to air, thus making it sufficiently robust for benchtop applications.